2011
DOI: 10.1093/annonc/mdq589
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tumor- and treatment-related factors on the development of local recurrence in osteosarcoma after adequate surgery. An analysis of 1355 patients treated on neoadjuvant Cooperative Osteosarcoma Study Group protocols

Abstract: Background: Local recurrence (LR) in osteosarcoma is associated with very poor prognosis. We sought to evaluate which factors correlate with LR in patients who achieved complete surgical remission with adequate margins. Patients and methods:We analyzed 1355 patients with previously untreated high-grade central osteosarcoma of the extremities, the shoulder and the pelvis registered in neoadjuvant Cooperative Osteosarcoma Study Group trials between 1986 and 2005. Seventy-six patients developed LR.Results: Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
72
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 43 publications
(31 reference statements)
10
72
3
7
Order By: Relevance
“…Canadell et al [5] performed transepiphyseal resection in 12 high-grade osteosarcomas and had one local recurrence in their series. Our incidence of local recurrences is similar to that observed in other patients with osteosarcomas treated with limb-sparing surgery with other techniques [2,5,8,12,14]. Ferrari et al [8] reported 18 local recurrences (8%) in 230 patients who had conservative surgery.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Canadell et al [5] performed transepiphyseal resection in 12 high-grade osteosarcomas and had one local recurrence in their series. Our incidence of local recurrences is similar to that observed in other patients with osteosarcomas treated with limb-sparing surgery with other techniques [2,5,8,12,14]. Ferrari et al [8] reported 18 local recurrences (8%) in 230 patients who had conservative surgery.…”
Section: Discussionsupporting
confidence: 87%
“…However, although we selected these patients with clinical and imaging parameters, six were not good responders, but the margins obtained were free of tumor and no other surgical approach was performed. Andreou et al [2] reported that patients participating in a study fared significantly better (p \ 0.0001) than those who were only registered and followed prospectively. This could be the cause of the higher patient survival in our series because although six patients were histologically poor responders, they could have other favorable characteristics such as small tumor size, adequate biopsy, or absence of soft tissue infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively small patient population, limited analysis of margins and the retrospective nature of the study prevent from further inference and speculation; all of these represent potential areas of opportunity for future research. However, even much larger, cooperative retrospective studies are unlikely to provide homogeneous data and definitive answers to the problem [1]. Prospective cooperative collection of homogeneous data related to the known risk factors, and including disease course after relapse and updated followup, should be pursued.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Local recurrence is the first sign of recurrent disease in approximately half of the cases, whereas it follows or presents synchronously with distant metastases in the remaining patients [1,3]. While isolated local recurrence after inadequate surgery presumably ''permits'' metastatic relapse, at least in some of the patients, its occurrence after a negative margin and in association with or shortly after distant metastasis suggests they both are signs of biologic aggressiveness.…”
mentioning
confidence: 99%